2014
DOI: 10.1002/chin.201408212
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: New Pterosin Sesquiterpenes and Antitubercular Constituents from Pteris ensiformis.

Abstract: Two new pterosin sesquiterpenes,13‐hydroxypterosin A (I) and 12‐hydroxypterosin Q (II) are isolated along with six known compounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Pterosins can be classified into three categories according to the number of skeletal carbon, such as 13 carbon, 14 carbon and 15 carbon pterosin derivatives [6,7]. Pharmacological investigations showed that pterosins had many bioactivities, such as antitumor, anti-inflammatory, anti-diabetes and anti-tuberculosis properties [8,9,10,11]. However, most studies on pterosins from this genus focused on Pteris multifida [7].…”
Section: Introductionmentioning
confidence: 99%
“…Pterosins can be classified into three categories according to the number of skeletal carbon, such as 13 carbon, 14 carbon and 15 carbon pterosin derivatives [6,7]. Pharmacological investigations showed that pterosins had many bioactivities, such as antitumor, anti-inflammatory, anti-diabetes and anti-tuberculosis properties [8,9,10,11]. However, most studies on pterosins from this genus focused on Pteris multifida [7].…”
Section: Introductionmentioning
confidence: 99%